Laporan Kasus: Drug-Induced Liver Injury (Dili) pada Anak - Emia Debora P. Karo-Karo; Samuel Eko Kristanto Kunta Adjie; Mikael Stevan jodjana (Malahayati Nursing Journal, 2026)
ABSTRACT Drug-Induced Liver Injury (DILI) is a form of liver injury that arises from the use of drugs that cause direct toxic effects or through idiosyncratic mechanisms that cannot be predicted in the pediatric population. The use of anti-tuberculosis drugs (Isoniazid, Rifampicin, and Pyrazinamide) is one of the main factors causing DILI in children that should be given special attention in clinical practice. Isoniazid can produce toxic metabolites, Rifampicin can increase enzyme induction which exacerbates the toxicity of Isoniazid, and Pyrazinamide carries a risk of hepatotoxicity. DILI is classified into hepatocellular, cholestatic, and mixed patterns. In this case report, a girl was found to have cholestatic type of DILI due to the use of anti-tuberculosis drugs. After two weeks of treatment, her SGOT and SGPT levels were found to be more than three times higher than normal. Physical examination revealed icteric sclera in both eyes, tenderness in the epigastric area and right upper quadrant, enlarged liver, and redness in both lower extremities. The patient received supportive therapy by discontinuing anti-tuberculosis drugs for 5 days, resulting in improvement and SGOT and SGPT returning to normal ranges. Subsequently, the patient was given gradual anti-tuberculosis drugs in the form of Rifampicin for 1 week. The patient relapsed and experienced DILI again, with SGOT and SGPT results increasing to 6 times the normal value. The patient was then referred to a type A hospital for further evaluation and management, thus confirming the importance of vigilance against DILI in pediatric patients receiving anti-tuberculosis drugs and the need for strict monitoring of liver function during therapy. Kata Kunci: Drug-Induced Liver Injury, Anti-Tuberculosis Drugs, Hepatotoxicity.  ABSTRAK Drug-Induced Liver Injury (DILI) merupakan bentuk cedera hati yang timbul akibat penggunaan obat yang menimbulkan efek toksik langsung maupun melalui mekanisme idiosinkratik yang tidak dapat diprediksi pada populasi pediatrik. Penggunaan Obat Anti-Tuberkulosis (OAT) (Isoniazid, Rifampisin, dan Pirazinamid) merupakan salah satu faktor utama terjadinya DILI pada anak yang harus menjadi perhatian khusus dalam praktik klinisi. Isoniazid dapat menghasilkan metabolit toksik, Rifampisin dapat meningkatkan induksi enzim yang memperberat toksisitas Isoniazid, serta Pirazinamid memiliki risiko hepatotoksisitas. DILI diklasifikasikan menjadi pola hepatoseluler, pola kolestatik, serta pola campuran. Dalam laporan kasus ini didapatkan seorang anak perempuan yang mengalami DILI tipe kolestatik akibat penggunaan OAT, setelah berobat selama 2 minggu hasil SGOT dan SGPT didapatkan meningkat 3 kali nilai normal. Pemeriksaan fisik menunjukkan adanya sklera ikterik pada mata kanan dan kiri, terdapat nyeri tekan pada area epigastrium dan kuadran kanan atas, hepar teraba membesar, serta terdapat kemerahan pada kedua ekstremitas bawah. Pasien mendapat terapi suportif dengan menghentikan OAT selama 5 hari, hasilnya pasien membaik, SGOT dan SGPT kembali ke rentang nilai normal. Selanjutnya pasien diberikan OAT bertahap berupa Rifampisin selama 1 minggu, pasien relaps mengalami DILI kembali, hasil SGOT dan SGPT meningkat 6 kali nilai normal. Pasien selanjutnya dirujuk ke rumah sakit tipe A untuk evaluasi dan penatalaksanaan lanjutan, sehingga kasus ini menegaskan pentingnya kewaspadaan terhadap DILI pada pasien pediatrik yang mendapat OAT serta perlunya pemantauan fungsi hati secara ketat selama terapi. Kata Kunci: Drug-Induced Liver Injury, Obat Anti-Tuberkulosis, Hepatotoksisitas.